2011
DOI: 10.1186/1471-2393-11-85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of midwife-led and consultant-led care of healthy women at low risk of childbirth complications in the Republic of Ireland: a randomised trial

Abstract: BackgroundNo midwifery-led units existed in Ireland before 2004. The aim of this study was to compare midwife-led (MLU) versus consultant-led (CLU) care for healthy, pregnant women without risk factors for labour and delivery.MethodsAn unblinded, pragmatic randomised trial was designed, funded by the Health Service Executive (Dublin North-East). Following ethical approval, all women booking prior to 24 weeks of pregnancy at two maternity hospitals with 1,300-3,200 births annually in Ireland were assessed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 23 publications
(37 reference statements)
4
54
2
3
Order By: Relevance
“…The frequency of operative vaginal delivery in our trial was lower than the 13 to 14% frequency in the meta-analysis by Schuit et al 20 Operative vaginal delivery is much more common in Europe than in the United States 23 where the current rate is approximately 3%. 24 In addition, two aspects of fetal heart-rate monitoring practice in Europe differ from the practice in the United States; in Europe, there is a slower horizontal scaling (1 cm per minute) on monitors (resulting in a compressed view that potentially affects the interpretation of heart-rate variability), and fetal blood sampling (for confirming or ruling out fetal acidosis) is more common.…”
Section: Discussioncontrasting
confidence: 71%
“…The frequency of operative vaginal delivery in our trial was lower than the 13 to 14% frequency in the meta-analysis by Schuit et al 20 Operative vaginal delivery is much more common in Europe than in the United States 23 where the current rate is approximately 3%. 24 In addition, two aspects of fetal heart-rate monitoring practice in Europe differ from the practice in the United States; in Europe, there is a slower horizontal scaling (1 cm per minute) on monitors (resulting in a compressed view that potentially affects the interpretation of heart-rate variability), and fetal blood sampling (for confirming or ruling out fetal acidosis) is more common.…”
Section: Discussioncontrasting
confidence: 71%
“…Thirteen of the 53 studies [21][22][23][24][25][26][27][28][29][30][31][32][33] compared the care provided by midwives with that provided by doctors working in a team with midwives. On meta-analysis, no significant difference in the antenatal hospitalization rate was found between care provided by midwives alone and that provided by doctors working with midwives (RR: 0.95; 95% CI: 0.79-1.13).…”
Section: Resultsmentioning
confidence: 99%
“…In Ireland, two alongside Midwife-led units (MLU) were introduced in 2004 and evaluated in a randomised controlled trial (RCT) 2004–2007, the MidU trial (ISRCTN14973283) [13]. Pregnant low-risk nulliparous and parous women were included.…”
Section: Introductionmentioning
confidence: 99%
“…They were transferred to the consultant-led unit (CLU) nearby if necessary and at any stage. The results showed that MLU care was as safe as consultant-led care that was provided to the control group [13] but was associated with fewer interventions, like having continuous electronic fetal monitoring or augmentation of labour. Midwife-led care also cost €182 less per woman [14], and resulted in greater satisfaction for some aspects of care [15].…”
Section: Introductionmentioning
confidence: 99%